Modulation of antioxidant enzymes, SIRT1 and NF‐κB by resveratrol and nicotinamide in alcohol‐aflatoxin B1‐induced hepatocellular carcinoma. Issue 1 (7th September 2020) - Rawat, Divya; Chhonker, Saurabh Kumar; Naik, Rayees Ahmad; Koiri, Raj Kumar
Abstract: Hepatocellular carcinoma (HCC) is the fifth most commonly diagnosed cancer worldwide and is associated with poor prognosis. The current study aimed to assess the therapeutic efficacy of resveratrol when administered alone and in combination with nicotinamide against alcohol‐aflatoxin B1‐induced HCC. Results reveal that during the development and progression of cancer, there was a decline in the level of antioxidant enzymes catalase, glutathione peroxidase, glutathione reductase (GR), antioxidant glutathione, and glutathione S ‐transferase, which is an enzyme of detoxification pathways. Treatment of resveratrol restored the level of catalase and glutathione peroxidase toward normal in alcohol‐aflatoxin B1‐induced HCC; however, nicotinamide worked in concert with resveratrol only in upregulating the activity of glutathione reductase, glutathione level, and glutathione S ‐transferase. SIRT1 agonist resveratrol was observed to modulate the activity of antioxidant enzymes by negatively regulating the expression of nuclear factor‐κB (NF‐κB) in alcohol‐aflatoxin B1‐induced HCC, thereby suggesting a cross‐talk between antioxidant enzymes SIRT1 and NF‐κB during the development and progression of HCC and its therapeutics by resveratrol and nicotinamide.